2021
DOI: 10.3389/fpls.2020.613325
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Predicting Complex Traits in Spring Wheat Breeding Program

Abstract: Genomic selection (GS) is transforming the field of plant breeding and implementing models that improve prediction accuracy for complex traits is needed. Analytical methods for complex datasets traditionally used in other disciplines represent an opportunity for improving prediction accuracy in GS. Deep learning (DL) is a branch of machine learning (ML) which focuses on densely connected networks using artificial neural networks for training the models. The objective of this research was to evaluate the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 66 publications
1
93
1
Order By: Relevance
“…Grain protein content and grain yield were accurately predicted when spectral data was collected at heading and grain filling stages, respectively (Sandhu et al, 2021b). Similarly, we observed that deep learning based GS models improve prediction accuracy by 3-5% in different agronomic traits in wheat (Sandhu et al, 2021a). The main objectives of this study were to 1) Optimize different MT machine and deep models for predicting grain yield and grain protein content in wheat, 2) Compare the performance of MT-GS and UT-GS models, and 3) Compare the performances of MT-GS mixed models with machine and deep models under cross-validation and independent validation scenarios.…”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…Grain protein content and grain yield were accurately predicted when spectral data was collected at heading and grain filling stages, respectively (Sandhu et al, 2021b). Similarly, we observed that deep learning based GS models improve prediction accuracy by 3-5% in different agronomic traits in wheat (Sandhu et al, 2021a). The main objectives of this study were to 1) Optimize different MT machine and deep models for predicting grain yield and grain protein content in wheat, 2) Compare the performance of MT-GS and UT-GS models, and 3) Compare the performances of MT-GS mixed models with machine and deep models under cross-validation and independent validation scenarios.…”
Section: Introductionsupporting
confidence: 55%
“…Deep learning based GS models gave 0-5% higher prediction accuracies for various agronomic traits in wheat in our previous work (Sandhu et al, 2021a). Montesinos-López et al (2018b) concluded that deep learning models were superior for six out of nine traits evaluated in maize and wheat over the traditional GBLUP.…”
Section: Potential Of the Machine And Deep Learning Models In A Breeding Programmentioning
confidence: 78%
See 3 more Smart Citations